Functional expression of the mechanosensitive PIEZO1 channel in primary endometrial epithelial cells and endometrial organoids - Hennes, Aurélie (Sci Rep, 2019)
Successful pregnancy requires the establishment of a complex dialogue between the implanting embryo and the endometrium. Knowledge regarding molecular candidates involved in this early communication process is inadequate due to limited access to primary human endometrial epithelial cells (EEC). Since pseudo-pregnancy in rodents can be induced by mechanical scratching of an appropriately primed uterus, this study aimed to investigate the expression of mechanosensitive ion channels in EEC. Poking of EEC provoked a robust calcium influx and induced an increase in current densities, which could be blocked by an inhibitor of mechanosensitive ion channels. Interestingly, RNA expression studies showed high expression of PIEZO1 in EEC of mouse and human. Additional analysis provided further evidence for the functional expression of PIEZO1 since stimulation with Yoda1, a chemical agonist of PIEZO1, induced increases in intracellular calcium concentrations and current densities in EEC. Moreover, the ion channel profile of human endometrial organoids (EMO) was validated as a representative model for endometrial epithelial cells. Mechanical and chemical stimulation of EMO induced strong calcium responses supporting the hypothesis of mechanosensitive ion channel expression in endometrial epithelial cells. In conclusion, EEC and EMO functionally express the mechanosensitive PIEZO1 channel that could act as a potential target for the development of novel treatments to further improve successful implantation processes.